Early-Life Stress Reprograms Stress-Coping Abilities in Male and Female Juvenile Rats - Pallarés, María Eugenia (2021)
Prenatal stress (PS) is a major risk factor for the development of emotional disorders in adulthood that may be mediated by an altered hypothalamic-pituitary-adrenal axis response to stress. Although the early onset of stress-related disorders is recognized as a major public health problem, to date, there are relatively few studies that have examined the incidence of early-life stressors in younger individuals. In this study, we assessed PS impact on the stress-coping response of juvenile offspring in behavioral tests and in the induced molecular changes in the hippocampus. Furthermore, we assessed if pregnancy stress could be driving changes in patterns of maternal behavior during early lactation. We found that PS modified stress-coping abilities of both sex offspring. In the hippocampus, PS increased the expression of bdnf-IV and crfr1 and induced sex difference changes on glucocorticoids and BDNF mRNA receptor levels. PS changed the hippocampal epigenetic landscape mainly in male offspring. Stress during pregnancy enhanced pup-directed behavior of stressed dams. Our study indicates that exposure to PS, in addition to enhanced maternal behavior, induces dynamic neurobehavioral variations at juvenile ages of the offspring that should be considered adaptive or maladaptive, depending on the characteristics of the confronting environment. Our present results highlight the importance to further explore risk factors that appear early in life that will be important to allow timely prevention strategies to later vulnerability to stress-related disorders.